New species of Limipolycystis Schilke, 1970 (Rhabdocoela: Kalyptorhynchia: Polycystididae) from the Western Mediterranean - Artois, Tom; Willems, Wim; Revis, Nathalie; Martens, Paul; Schockaert, Ernest (Zootaxa, 2012)
Five new species of Limipolycystis Schilke, 1970 are described and their morphology is compared to that of the only spe-cies known, L. curvitubo Schilke, 1970. L. sicilicula n. sp., L. falx n. sp., L friedae n. sp., L. libra n. sp. and L. wallbergin. sp. all largely resemble L. curvitubo as to the internal anatomy. They all have a caudally-situated testis and, at least inthose species for which good material is available, a seminal receptacle could be seen. This seminal receptacle is tubiform,connecting the bursa with the most proximal part of the oviduct, which is filled with sperm. All these species are mainlydistinguishable from each other by details in the shape of the stylet. Diagnoses are provided for all new species and the diagnosis of the genus is emended to reflect the new finds.